OLAH RAGA, OLAH RASA DAN OLAH PIKIRAN MELALUI ASANA YOGA - Astuti, Ketut Wendi (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2019)
The outbreak of global materialism and consumerism has eroded human noble values, even reaching and reaching remote villages. Conditions in today's modern era, humans are faced with various kinds of challenges and difficulties that make humans full of increasingly heavy pressures, which results in various kinds of changes, mental, and also various forms of protection and assistance that deviate. This phenomenon occurs everywhere from cities to remote villages. No exception this phenomenon also occurs on the island of Bali which is famous for its tourism area. Its appearance is a case of medical illness, a disease related to its non-medical illness, as well as thought thoughts and presented thus. Education is a part of human life that leads people to become intelligent and virtuous human beings. Responding to the various problems mentioned above, the issues raised in this study are: Does the practice of yoga asanas have an effect on exercise, taste, and mind processing. While the goal to be achieved is to find out the influence of uasan asanas training on sports, taste, and mind processing.The method used to collect data is the observation method of participation, the method of in-depth interviews and literature study. While the theory used in analyzing data is the reception theory From the results of the study it can be seen that: Asanas yoda is implemented with a variety of movements consisting of movements in a standing position, in a sitting position and in a sleeping position. All the yoga asanas movements harmonize and unite body movements with feelings, breath and mind.